The Performance Appraisal Analysis of Employee at Bina Mandiri Gorontalo Foundation - Sitti Husna Noviana Djou; Imam Mashudi (LP2M Universitas Bina Mandiri Gorontalo, 2020)
The purpose of this study is: 1) to find out and analyze how the implementation of employee performance appraisal at the Bina Mandiri Gorontalo Foundation; 2) to find out what factors are hampering the implementation of employee performance appraisal at the Bina Mandiri Gorontalo Foundation. This research uses a qualitative approach and the type of research used is descriptive qualitative. Data sources used are primary data sources and secondary data sources. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used: data collection, data reduction, data presentation, and concluding. The result of the research shows that the implementation of employee performance appraisal at the Bina Mandiri Gorontalo Foundation based on 7 (seven) performance evaluation indicators can be said to be not yet fully appropriate. Three categorized indicators are by performance appraisal, namely obedience, honesty, and cooperation. Meanwhile, the indicators of leadership, responsibility, and achievement are not appropriate because in the performance evaluation that indicators still less influential. And, the initiative is categorized as inappropriate because in the performance evaluation it does not become a benchmark in performance appraisal. The factors that hampered the implementation of performance appraisal at the Bina Mandiri Gorontalo Foundation were seen from seven factors. Based on the results of the research five factors hinder the performance evaluation, are lack of objectivity, halo effect, Leniency, Strictness, and Personal Prejudices. While the other two factors, i.e. Central Tendency and Recent Behavior Bias is inappropriate because these two factors did not hamper the implementation of performance appraisal at the Bina Mandiri Gorontalo Foundation.